Intonational means of expressing finality in Tuvan folklore narration - Татьяна Раисовна Рыжикова; Илья Михайлович Плотников; Альбина Альбертовна Добрынина; Чойган Геннадиевич Ондар (Novye Issledovaniâ Tuvy)
The present study is as a continuation of our previous work on Tuvan intonation, which was concerned with prosodic markers as means of structuring a folklore text. The purpose of this article is to examine the manifestation of intonational universals associated with the expression of completeness in Tuvan narrative utterances, which has not previously been subjected to a dedicated analysis employing corpus and statistical methods. The theoretical and methodological basis of the study is formed by the principles that have been established in Russian linguistics, including identifying language-level oppositions between intonational units and a multi-aspect analysis of the utterance as a syntactic unit.